From Pyrrho to Sextus Empiricus: The Philosophical Roots of Postmodern Political Theory in Ancient Greek Skepticism - Kirac, Ziya Kivanc; Kargioglu, Firat; Goktolga, Oguzhan (Mdpi, 2025)
In this article, the philosophical (critical) continuity between ancient Greek skepticism (Pyrrhonism) and postmodern political theory is pointed out. This continuity (philosophical reincarnation) is demonstrated by referring to Sextus Empiricus' writings on Pyrrhonism, as well as two different approaches that are considered to reflect postmodern political theory in its most salient features, such as anti-fundamentalism: Chantal Mouffe's project of radical democracy and the art of doubt in Ulrich Beck's reflexive modernity. The content of the identified continuity is basically the following: Just as the Pyrrhonian philosopher aspires to achieve serenity of spirit by suspending judgment through doubt (epoche and ataraksia) [epeke -alpha tau alpha rho alpha xi iota alpha], the postmodern theorist aims to end organized political violence by doubting all modern truth allegations. In other words, the individual hope of the Pyrrhonian philosopher is reproduced in the postmodern mind as a socio-political ideal. In Michel Foucault's terms, the regime of truth or the politics of truth is an option that often leads to the terror of truth. The politics of doubt, on the other hand, is a peaceful, tolerant alternative. According to the postmodern theorist, skepticism is a highly strategic element of a pluralist (libertarian) democratic order. The intellectual way to make modern democracy even more democratic is, first and foremost, through a skepticism that makes absolutely no concessions to truth allegations. In this respect, the most uncompromising skeptic in the history of philosophy is the Pyrrhonian philosopher. Pyrrhonism is the summit of anti-dogmatism. This means that the postmodern theorist is not so much a postmodern agent. In other words, postmodern political theory is the theory of an innovation that is already obsolete.
Keywords: Pyrrhonism; Sextus Empiricus; postmodern political theory; Chantal Mouffe; Ulrich Beck